The impact of TLR2 Gene variant (RS5743708) on the Genetic Susceptibility to Polycystic Ovary Syndrome: An Analytical Study - Hafsa Noreen, Huma Sattar, Munawar Afzal, Sehrish Waseem, Tahira Anwar, Rakhshanda Jabeen, Zainab Maheen, Sehrish Firyal (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Polycystic ovarian syndrome is a common endocrinopathy that involves excess androgen and infertility due to anovulatory factors. This syndrome is also linked to several conditions including obesity and high insulin levels as well as an increased risk of cardiovascular complications. Aims and Objective: The main objective of this research is to examine the molecular function of the TLR2 gene (rs5743708) polymorphism in Pakistani women who have been recognized as having PCOS based on the Rotterdam criteria. This polymorphism in the TLR2 gene is investigated for its association with PCOS in women. Methodology: This case-control study recruited 40 patients. Blood samples were collected from 30 patients diagnosed with PCOS and 10 from non-PCOS. The blood samples were placed in an EDTA tube for molecular analysis. After the genomic DNA extraction, the polymerase chain reaction method was used to identify the (rs5743708) polymorphism. Results: To validate the PCR results, sanger sequencing was performed commercially. The phylogenetic tree was constructed to provide a visual summary of the genetic diversity of the TLR2 gene among PCOS patients from different regions. Our findings indicate that the analysis of the genetic association between the TLR2 gene (rs5743708) polymorphism and PCOS in a Pakistani population showed no significant correlation. Conclusion: The identification of genetic association may unveil novel therapeutic targets. Targeting the TLR2-related molecular mechanism influenced by this polymorphism could lead to the development of more effective and personalized treatment strategies for PCOS among Pakistani women. Keywords: Genetic association, POCS, TLR2, Polymorphism, rs5743708